Influence of glide path kinematics during endodontic treatment on the occurrence and intensity of intraoperative and postoperative pain: a systematic review of randomized clinical trials - Thaís Christina Cunha; Felipe de Souza Matos; Luiz Renato Paranhos; Ítalo de Macedo Bernardino; Camilla Christian Gomes Moura (BMC, 2020)
Abstract Background Preliminary canal enlargement (glide path preparation) may play a significant role in the development of pain. The aim of this systematic review of randomized clinical trials was to assess the influence of glide path kinematics during endodontic treatment on the occurrence and intensity of intraoperative and postoperative pain. Methods A search was performed in June 2019 in six electronic databases (PubMed, Scopus, LILACS, SciELO, Embase and Web of Science) and two grey literature databases (OpenGrey and OpenThesis). The bibliographic references of the eligible articles were also hand-searched. The included clinical studies assessed the occurrence and intensity of intraoperative and/or postoperative pain after root canal preparation without glide path preparation (WGP) or with glide path preparation using manual (M-GP), continuous rotary (CR-GP), or reciprocating (R-GP) instruments. The primary outcome was the occurrence and intensity of intraoperative and postoperative pain, while analgesic consumption was the secondary outcome. The full texts of the eligible studies were analyzed by two reviewers who performed calibration exercises to verify the risk of bias and quality of the individual studies using the Joanna Briggs Institute Critical Appraisal tool. Results From 1283 identified articles, only six studies were included in the qualitative analysis of the results, with a total sample of 884 patients/teeth. Three studies presented a high risk of bias, while three studies presented a moderate risk. Two studies reported that CR-GP causes lower pain levels than M-GP and WGP, and three studies showed no differences between CR-GP and R-GP. Regarding analgesic consumption, two studies found no differences among glide path kinematics, and one study reported lower consumption for CR-GP than for M-GP. Because of the limited number of studies and methodological differences, no statistical analyses were performed for the glide path kinematics comparisons. Conclusions Compelling evidence indicating a significantly different occurrence and intensity of pain among glide path kinematics is lacking. The systematic review protocol was registered in the PROSPERO database [CRD42020139989].